1999
DOI: 10.1080/146392499300622
|View full text |Cite
|
Sign up to set email alerts
|

First basic performance evaluation of the XE-2100 haematology analyser

Abstract: T he new ly developed X E-2100 haematolog y analyser can provide complete blood counts, leukocyte diå erentials, perform reticulocyte analysis, and obtain quantitative data on nucleated red blood cells ( N RBCs) . In this study, we evaluated the basic perf ormance of this instrument using routinely obtained blood specimens treated with ethylenediaminetetraacetic acid-2K . Reproducibility, carryover, stability during storag e at 4 ë C and room temperature, and accuracy were evaluated. In this evaluation, repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…While other publications showed that the %RETI remained stable for 48 h only (Robinson, Mangin & Saugy, 2004; Voss et al. , 2008), we could not identify under the conditions of our investigation, any significant changes for the investigated variables even after 72 h of storage at approximately 4 °C (Tsuda et al. , 1999; Lippi et al.…”
Section: Discussioncontrasting
confidence: 79%
“…While other publications showed that the %RETI remained stable for 48 h only (Robinson, Mangin & Saugy, 2004; Voss et al. , 2008), we could not identify under the conditions of our investigation, any significant changes for the investigated variables even after 72 h of storage at approximately 4 °C (Tsuda et al. , 1999; Lippi et al.…”
Section: Discussioncontrasting
confidence: 79%
“…Limiting our search to studies that used automated analyzers (last 20 years), we found 15 studies that provide stability results of FBCs depending on CAT and mean temperature (T) A total of 154 CAT‐T pairs were found in these studies. These pairs were assessed as ‘stable’ (green markers in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stability assessment of RBC indices according to the collection to analysis time (CAT) and mean storage temperature (T). One hundred and fifty‐four CAT‐T pairs obtained from 15 studies are displayed in green when no or minimal degradation in the RBC parameters was observed and in red when non‐negligible degradation was observed (Square: . Dot: .…”
Section: Resultsmentioning
confidence: 99%